Pterosaurs : flying contemporaries of the dinosaurs - Veldmeijer, A. J. (Sidestone Press, 2012)
Pterosaurs or flying reptiles were the first vertebrates to evolve flight. These distant relatives of modern reptiles and dinosaurs lived from the Late Triassic (over 200 million years ago) to the end of the Cretaceous (about 65 million years ago) a span of some 135 million years. When they became extinct, no relatives survived them and as a result these prehistoric animals cannot readily be compared with our modern-day fauna. So what do we know of these highly succsessful animals? The present summary answers this and many more questions based on the most recent results of modern scientific re.